Utility functions, fiscal shocks and the open economy: In the search of a positive consumption multiplier - Philipp Wegmueller (University of Bern, Department of Economics, 2014)
This paper analyzes the dynamic effects of a fiscal policy shock and its transmission mechanism in a small open economy and compares the responses under different specifications of the utility function. The traditional Mundell-Flemming model tells that fiscal policy is more effective under a peg than under a float. This result is not confirmed for a baseline small open economy model with separable preferences. The present paper offers a survey of non-separable utility found in the literature on fiscal policy shocks and compares their implications for the transmission mechanism. The aim is to overturn the negative wealth effect of an increase in government spending, which causes a decrease in private consumption under the baseline separable utility function. Using a plausible calibration of the model, I find that if the complementarity between consumption and hours worked is large enough, then the response of private consumption is likely to be positive, although the assumptions have to be strong. This result holds for any specification of exchange rate regime.
Keywords: E52; E62; F41; 330; Fiscal Shocks; Non-Separable Utility; Exchange Rate Regimes; Private Consumption